Mucoadhesive systems in dentistry: A review - Rath, Rishi; Tevatia, Siddharth; Rath, Anukriti; Behl, Ashish; Modgil, Vishal; Sharma, Nikhil (International Journal of Dental Research, 2016)
For any treatment plan to succeed, two factors are paramount correct selection and application of pharmacologic agents and patient compliance. But what happens when both these are followed judiciously, but the medicine itself does not stay long enough to finish its action? Then we need something that will make the medicine stick literally. That is when bioadhesives have their say. Long-term adhesion of drugs to the oral mucosa is usually prevented by the continuous salivary flow and the mechanical movements of the tongue. Therefore, formulations acting as vehicle for local drug delivery to the oral mucosa need to have excellent mucoadhesive properties. The present article reviews mucoadhesive systems with various formulations that can be used in dentistry to improve local drug delivery.